Urgensi Regulasi Pendampingan Psikologis dalam Eksekusi Putusan Hak Asuh - Delzanty, Kayla; Taupiqqurrahman, Taupiqqurrahman (Universitas Semarang, 2025)
This study examines the urgency of regulating psychological assistance in the execution of child custody decisions as non-material subjects within Indonesian civil procedural law. The absence of standardized execution mechanisms in the Herziene Indonesisch Reglement (HIR) has resulted in low enforceability of custody rulings, repeated execution failures, and potential violations of the best interests of the child principle. This research employs a normative juridical method using statutory, case, and conceptual approaches, with analysis of the Tsania Marwa–Atalarik Syach custody dispute and the Cibinong Religious Court Decision Number 5594/Pdt.G/2020/PA.Cbn. The findings demonstrate that children’s resistance during execution constitutes a psychological response that cannot be addressed solely through coercive legal measures; without professional assessment and assistance, custody decisions tend to become non-executable and risk causing psychological trauma. The novelty of this study lies in proposing a hybrid legal–psychological model that positions forensic psychological assessment as a judicial prerequisite for custody execution. This study concludes that institutionalizing psychological assistance through a Supreme Court Regulation is essential to ensure effective enforcement, safeguard children’s rights, and restore the credibility of civil justice. Penelitian ini mengkaji urgensi pembentukan regulasi pendampingan psikologis dalam pelaksanaan eksekusi putusan hak asuh anak sebagai subjek non-materiil dalam hukum acara perdata Indonesia. Ketiadaan mekanisme baku dalam Herziene Indonesisch Reglement (HIR) menyebabkan rendahnya daya laku putusan, kegagalan eksekusi berulang, serta potensi pelanggaran asas kepentingan terbaik bagi anak. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan peraturan perundang-undangan, kasus, dan konseptual, melalui analisis terhadap sengketa hak asuh Tsania Marwa–Atalarik Syach dan Putusan Pengadilan Agama Cibinong Nomor 5594/Pdt.G/2020/PA.Cbn. Hasil penelitian menunjukkan bahwa resistensi anak dalam proses eksekusi merupakan respons psikologis yang tidak dapat diselesaikan melalui mekanisme koersif semata, sehingga tanpa asesmen dan pendampingan profesional, putusan pengadilan cenderung menjadi non-executable dan berisiko menimbulkan trauma psikologis pada anak. Kebaruan penelitian ini terletak pada perumusan model hibrida hukum–psikologi yang memposisikan asesmen psikologis forensik sebagai prasyarat yustisial dalam eksekusi putusan hak asuh. Penelitian ini menyimpulkan bahwa pembentukan Peraturan Mahkamah Agung tentang pendampingan psikologis sebelum eksekusi merupakan kebutuhan mendesak guna menjamin efektivitas putusan, perlindungan hak anak, serta pemulihan kewibawaan peradilan perdata.